Polysemy Analysis of Song Lyrics In Ed Sheeran’s Album “Divide” - Luli, Andre Hisbah Ghalib; Bay, Indri Wirahmi; Ali, Sri Widyarti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Polysemy, the phenomenon where a single word carries multiple related meanings, is a fundamental aspect of semantics that plays a crucial role in language interpretation. In song lyrics, polysemy allows for layered meanings, enriching the emotional depth and artistic expression of music. This study examines the presence of polysemy in Ed Sheeran’s album Divide, analysing how words with multiple meanings contribute to the lyrical depth of his songs. The album features numerous instances of logical polysemy, where words retain different but interconnected meanings, enhancing the storytelling and emotional impact of the lyrics. By analysing various songs from Divide, this study aims to highlight Sheeran’s use of polysemy as a stylistic and poetic device. Recognizing polysemy in music not only aids in accurate interpretation but also deepens the emotional connection between the artist and the audience.